Análise da função sexual de mulheres vivendo com HIV - Dantas, Maiara Bezerra (2024)
Antiretroviral Therapy (ART) increased the survival of People Living with HIV (PLHIV), and other aspects of these patients' lives began to be studied, such as sexual function. Therefore, this study was proposed, with the general objective of analyzing the sexual function of women with HIV. This is a cross-sectional, descriptive and quantitative study, carried out in four institutions in Fortaleza, Ceará: São José Hospital, Walter Cantídio University Hospital, José de Alencar Polyclinic and Support House of the National PLHIV Network. The sample consisted of 387 participants and included women over 18 years of age, with positive anti-HIV serology and using ART for more than three months. The exclusion criteria were: trans women, pregnant women and disabling physical or mental illness. Data collection took place from January to December 2023, through interviews in a private office, using the following instruments: Sociodemographic, Epidemiological, Behavioral and Clinical Form for PLHIV and the Female Sexual Function Index (FSFI). In data analysis, descriptive statistics and univariate and multivariate logistic regression analysis were performed, considering a P value < 0.05 to be statistically significant. SPSS and R software were used for analysis. The study was approved by the Research Ethics Committee of the Federal University of Ceará, on 07/12/2022, under protocol No. 5.800.133 and by the co-participating institutions. The participants signed the Free and Informed Consent Form. Of the 387 women with HIV, 217 were sexually active and 170 were inactive, and the analysis of the two strata was carried out separately. Among sexually active women, the majority were under 45 years old (56.6%), mixed race (67.7%), with a partner (53.0%), more than 8 years of study (61.2%), two or fewer children (61.2%), without a job (37.7%) or retired/on leave/sickness benefit ( 34.5%), income lower than the minimum wage (70.0%), sexual exposure category (93.0%), no casual partnership (87.5%), used contraceptive method (52.5%), consumed alcohol (63.1%), did not exercise (62.2%), CD4+ T lymphocyte count greater than 350 cells/mm3 (80.1%), undetectable viral load (81.1%) and had been on ART for more than 8 years (54.8%). The prevalence of sexual dysfunction was 53.0% (confidence interval - 95% CI: 46.36-59.53). The average FSFI total score was 25.28, and by domains it was: desire (3.69), excitement (4.01), lubrication (4.36), orgasm (4.25), satisfaction (4, 53) and pain (4.44), indicating sexual dysfunction in the total score and by domains. In the multivariate logistic regression analysis, the following were associated with sexual dysfunction: being unemployed (P=0.0131) and away from work (P=0.0049), respectively 2.46 and 2.93 times more likely compared to those who have job; not having a casual partner (P=0.0386), 2.55 times more likely than those who did; use a contraceptive method (P=0.0247), except condoms, 1.94 times more likely compared to those who did not use it. As for sexually inactive women, the majority were over 45 years old (75.8%), mixed race (65.2%), without a steady partner (82.3%), less than 8 years of education (55.8%), two or fewer children (53.5%), unemployed (31.7%) or retired/on leave/sickness benefit (54.7%), income lower than the minimum wage (74.1%), category of sexual exposure (93.0%), without steady (75.8%) and casual partners (85.8%), used contraceptive method (54.1%), did not exercise (72.9%), count of CD4+ T lymphocytes greater than 350 cells/mm3 (79.4%), undetectable viral load (85.8%) and ART for more than 8 years (65.2%). The prevalence of hypoactive sexual desire was 94.12% (95%CI: 89.51-96.77), which was assessed by the Desire domain of the FSFI, with an average score of 2,18. In the multivariate logistic regression analysis, brown skin color (P=0.0143) was associated with hypoactive sexual desire, but this finding should be viewed with caution, due to the high prevalence of hypoactive sexual desire in the sample. It is concluded that there was a high prevalence of sexual dysfunction and hypoactive sexual desire among women living with HIV.